Understanding the relationship between emotional child abuse and workplace dysfunction - Tuthill, Oliver W.; Scimeca, Roy T. (Sherborn, MA: Aquarius Health Care Videos, 2000)
This program explores the relationships and interconnections of child abuse and later workplace dysfunction. This video is for employers and employees to view
Psychological consultant, Jordan Robinson
Keywords: Psychology, Pathological; Social Behavior Disorders -- Psychology; Abused children -- Mental health; Social Behavior Disorders